Tarekat “Semi Mandiri”: Prototipe Ritual Masyarakat Pedesaan Madura - Imam Amrusi Jailani (Ulumuna, 2010)
This study explores the phenomena of studying local rituals in Islam, which often become a focus of scholarly research. The studies of local Islam often reveal the map and the sketch of the developed various local rituals of Islam such as tarekat, tahlil and slametan. Scholars and experts have attempted to research these phenomena and employed diverse approaches to explain them. Most of them used textual and contextual approaches. Others sought to use structural and functional approach. Their study help explain the pattern and the attitude of Islamic rituals among certain people. One example pertains to the explanation of the most rural people, especially in Madura East Java regarding their practice of local Islam. One of the fundinds of such scholalrly research asserts that the poeple in the region conduct their rituals independently, without a medium of teachers and pupils.